Pale blue dot - Chin, Li Zhi (2015)
et to the words of Carl Sagan, Pale Blue Dot is an animation that situations human history against the tapestry of the cosmos. Using a eclectic combination of art styles woven seamlessly together through music and visuals, the animation seeks to remind us that regardless of our differences, we are one species living together on the planet we call Earth.